Оценка качества продуктов животноводства - Житенко Петр Васильевич (Россельхозиздат, 1987)
Экземпляры: КХ (20100909) / Инвентарный номер: 897637 / Цена: 0.50 / Сис.шифр: 65.9(2)32-82 / Авт.знак: Ж 74 / ГРНТИ: 68 / ББК: 65.325.2